2019
DOI: 10.1002/aoc.4874
|View full text |Cite
|
Sign up to set email alerts
|

Platinum(II) complexes bearing bulky Schiff base ligands anchored onto mesoporous SBA‐15 supports as efficient catalysts for hydrosilylation

Abstract: Reported herein is an easy-to-prepare novel heterogeneous catalyst of platinum complexes bearing binary ligands of bidentate naphthalenolimine and cyclo-1,5-octadiene that are anchored onto mesoporous silica SBA-15. The presence of the binary ligands not only stabilized the platinum, but also enabled the platinum atoms to form nanoclusters with diameters of ca 1 nm, and led to high platinum loading (8.69 wt%). Moreover, the platinum catalyst exhibited high catalytic activity towards hydrosilylation of terminal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The MNP-AF-Pd catalyst showed higher catalytic activity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Some of the catalyst's key benefits are the use of a green solvent, moderate reaction conditions, a short reaction time, reusability for other reactions, and its ease of recovery from the reaction mixture.…”
Section: Comparison Of Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…The MNP-AF-Pd catalyst showed higher catalytic activity. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] Some of the catalyst's key benefits are the use of a green solvent, moderate reaction conditions, a short reaction time, reusability for other reactions, and its ease of recovery from the reaction mixture.…”
Section: Comparison Of Catalystsmentioning
confidence: 99%
“…In order to create a heterogeneous catalyst that is adaptable, stable, strong, and efficient without interfering with its catalytic sites, a variety of supports have been employed. [7][8][9][10] The suitability of support with the metal complexes and the solvents is also a crucial component of the catalytic method because it affects the recyclability, activity, and stability of supported metallic catalysts. [10][11][12] Notable, iron oxide nanoparticles have shown good support for metal catalysts because of high surface to volume ratio, which can offer a lot of active sites to encourage catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%
“…The immobilized Pt catalyst is active with respect to the hydrosilylation of alkenes under UV irradiation (Scheme ). Recently, Huo et al reported a Pt­(II) complex with bulky Schiff base ligands . This catalyst system is also applicable to the hydrosilylation reaction: a maximum TON of 3623 was obtained from the reaction of 1-octene and trimethoxyhydrosilane.…”
Section: Isolated Metal Complex For Enhanced Catalysismentioning
confidence: 99%
“…Recently, Huo et al reported a Pt(II) complex with bulky Schiff base ligands. 43 This catalyst system is also applicable to the hydrosilylation reaction: a maximum TON of 3623 was obtained from the reaction of 1octene and trimethoxyhydrosilane.…”
Section: Isolated Metal Complex For Enhanced Catalysismentioning
confidence: 99%
“…22 Compared to MCM-41, SBA-15 possesses thicker framework walls, higher hydrothermal stability, and much bigger pore diameter between 5 and 30 nm, which can facilitate diffusion of organic molecules inside the channels. 23 Although mesoporous SBA-15-supported iridium, palladium, platinum, and rhodium complexes have been successfully applied for some important organic reactions, 24 the synthesis and applications of SBA-15-immobilized gold complexes have not been explored until now. We herein report the synthesis of an SBA-15-supported strongly hindered NHC–gold( i ) complex [IPr-SBA-15-AuNTf 2 ] and its catalytic behavior in gold( i )-catalyzed heterocyclization between ynamides and benzyl or indolyl azides leading to valuable 2-aminoindoles or 3-amino-β-carbolines (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%